GRAPHENE OXIDE NANOPARTICLES IN THE REGULATION OF THE OXIDATIVE ACTIVITY OF HUMAN MONOCYTES - S. V. Uzhviyuk (SPb RAACI, 2021)
Graphene-based materials have an opportunity for use in biomedicine, thanks to their properties. Nevertheless, due to its cytotoxic effects, the use of graphene-based drugs is problematic. However, the surface modification of graphene oxide (GO) nanoparticles with a polyethyleneglycol (PEG) is one way to reduce the harmful effects of graphene on cells. Applying nanoparticles implies their interaction with the immune system, which protects the body. Monocytes are innate immunity cells and the first line of defenсe of the human organism from microorganisms and other alien objects. One of the monocytes’ reactions to a stimulus of any nature is to produce reactive oxygen species (ROS). Published data shows an incomplete picture of modified graphene oxide nanoparticles’ effects on ROS formation by human monocytes. Thus, it was essential to evaluate the pegylated graphene oxide (GO-PEG and GO-8armedPEG) effect on ROS production by human monocytes, assessed by the luminol-dependent chemiluminescence (LCL). The objects of the study were CD14+-cells isolated from mononuclear cells of healthy donors. ROS production was stimulated by opsonized zymosan (OZ), spontaneous LCL was used as a control. PEG-modified (GO-PEG and GO-8armedPEG) GO nanoparticles with sizes of 100-200 nm (“small”) and 1-5 μm (“big”) with PEG covering ~ 20% were used at concentrations of 5 and 25 μg/ml. The study showed that small size nanoparticles at a low concentration of 5 μg/ml and big nanoparticles coated with 8-armed PEG at both concentrations have a significant suppressive effect on spontaneous ROS production. In the stimulated LCL reaction variant, it was found that small nanoparticles (25 μg/ml) also have a suppressive effect on ROS production, such as big-sized particles coated with linear PEG at the same concentration. Thus, we have established for the first time that graphene oxide nanoparticles functionalized with PEG are capable of inhibiting the ROS production by human monocytes, and therefore, we can speak of the antioxidant activity of GO-PEG.